Patterns of Kinship Address Term Usage in the Malay Families of Marok Kecil Village: A Sociolinguistic Study - Siti Nuraini Wahidatun Nisa; Cece Sobarna; Asri Soraya Afsar (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the patterns of kinship address term usage within the family interactions of the Malay community in Marok Kecil Village, Lingga Regency, Riau Islands. Using a descriptive qualitative method, the research examines how speakers choose address terms based on relational roles such as age, kinship status, and social hierarchy. Data were collected through observation, audio recordings, field notes, and structured interviews with 100 participants from 50 families, covering a range of age groups and kinship positions. The findings reveal three dominant usage patterns: nonreciprocal downward (older to younger), nonreciprocal upward (younger to older), and symmetrical reciprocal (among peers). The choice of address terms is shaped by factors such as generational differences, situational formality, and sociocultural norms. The study employs Ervin-Tripp’s (1972) alternation and co-occurrence rules to interpret how linguistic behavior reflects familial roles and traditional values in the Riau Malay context. These findings contribute to a deeper understanding of how language is used to encode social relationships and maintain cultural continuity within traditional family systems.